2006
DOI: 10.1063/1.2397027
|View full text |Cite
|
Sign up to set email alerts
|

Determination of vibrational modes in electron energy loss spectroscopy of polycrystalline diamond surfaces by isotopic exchange

Abstract: The high resolution electron energy loss spectrum of polycrystalline diamond films deposited from various isotopic gas mixtures, C12H4+H2, C12D4+D2, and C13H4+H2, are reported. Three types of peaks were unambiguously identified: (1) Pure C–C related peaks (a diamond C–C stretch at ∼150meV and its overtones at 300, 450, and 600meV), (2) pure C–H related peaks (C–H bend at ∼150meV and C–H stretch of sp3 carbon at 360meV), and (3) coupling of C–H and C–C peaks (∼510meV peak due to coupling of the C–H stretch at 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 45 publications
(34 citation statements)
references
References 21 publications
2
32
0
Order By: Relevance
“…The first two peaks are associated with (111) and (100) diamond surfaces, the third and fourth peaks are attributed to sp 2 and sp hybridized carbon from the surface or grain boundary regions, respectively [38,39]. An extensive discussion about these spectral components can be found elsewhere [40,41]. The peaks at $305 and 450 meV are due to pure C-C vibrations, associated with the first and second overtones of diamond optical phonon located at $156 meV.…”
Section: à2mentioning
confidence: 99%
“…The first two peaks are associated with (111) and (100) diamond surfaces, the third and fourth peaks are attributed to sp 2 and sp hybridized carbon from the surface or grain boundary regions, respectively [38,39]. An extensive discussion about these spectral components can be found elsewhere [40,41]. The peaks at $305 and 450 meV are due to pure C-C vibrations, associated with the first and second overtones of diamond optical phonon located at $156 meV.…”
Section: à2mentioning
confidence: 99%
“…[51][52][53][54]57,58,[62][63][64][65][66][67] In order to clarify the origin of the peaks at 300, 450, and 600 meV, an ion irradiation experiment was performed on a well-defined diamond surface. [74,75] Ion irradiation results in partial amorphization of the film surface, so the change in the shape of the spectrum following the ion irradiation may be associated with the change of the surface crystalline structure. Our results show that the intensity of these three overtone HREEL peaks (300, 450, and 600 meV) decreases most significantly after the diamond surface has been irradiated with low energy Ar ions.…”
Section: Hreels Mode Positionmentioning
confidence: 99%
“…10 The morphology of the samples was studied using AFM ͑Nanoscope IV MultiMode from Veeco͒ operated in tapping mode. 7 It is observed that following MW hydrogen plasma treatment ͓Fig. Figure 1 shows the HREELS measurements of the CVD diamond film before and after exposures.…”
mentioning
confidence: 99%